Method for manufacturing purified quaternary ammonium compound aqueous solution

By using a cation exchange resin with a crosslinking degree of 8 or higher to treat aqueous solutions of crude quaternary ammonium compounds, the method effectively reduces metal impurities to acceptable levels, addressing the limitations of existing purification methods and ensuring high throughput efficiency.

JP2025069473AInactive Publication Date: 2025-05-01TOKUYAMA CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022032643
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-03
Publication Date
2025-05-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for purifying aqueous solutions of quaternary ammonium compounds are insufficient in reducing metal impurities to acceptable levels, especially in high-throughput applications, leading to potential defects in semiconductor manufacturing.

Method used

A method involving contact between the aqueous solution of crude quaternary ammonium compounds and a cation exchange resin with a specific degree of crosslinking, specifically 8 or higher, to effectively adsorb and remove metal ions, maintaining high removal efficiency even at high throughputs.

Benefits of technology

The method achieves excellent reduction of metal ions in the aqueous solution, maintaining high efficiency even with large volumes of the crude quaternary ammonium compound solution, making it suitable for industrial-scale purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069473000001
    Figure 2025069473000001
  • Figure 2025069473000002
    Figure 2025069473000002
  • Figure 2025069473000003
    Figure 2025069473000003
Patent Text Reader

Abstract

To develop a method whereby it is possible to maintain a high removal effect of metal ions from a crude quaternary ammonium compound (for example, a quaternary ammonium hydroxide compound or halogenated quaternary ammonium compound) aqueous solution having a low content of organic impurities, even if the removal is continued for a large processing amount thereof.SOLUTION: This method for manufacturing a purified quaternary ammonium compound aqueous solution uses a crude quaternary ammonium compound aqueous solution which contains metal impurities and in which the content of organic impurities having a molecular weight per mole of at least 1000 is 1000 ppm or less, the method being characterized by bringing the crude quaternary ammonium compound aqueous solution into contact with a cation exchange resin having a degree of crosslinking of at least 8, preferably 11-30, and having counter ions which are non-metallic ions.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a purified aqueous solution of a quaternary ammonium compound, and more particularly to the method for reducing the content of metal impurities in an aqueous solution of a crude quaternary ammonium compound that contains the metal impurities as impurities. [Background technology]

[0002] Quaternary ammonium compounds are used in phase transfer catalysts, surfactants, disinfectants, etc. In particular, quaternary ammonium hydroxide compounds, such as tetramethylammonium hydroxide, are used as a pH adjuster, or in the form of an aqueous solution for cleaning, etching, and developing solutions during semiconductor manufacturing, as a type of organic alkali that exhibits strong basicity. In such semiconductor-related processing agent applications, as integration progresses, metal impurities, if remaining on the surface of electronic devices, can cause defects, so it is required to reduce them as much as possible. More specifically, it is desired to reduce the content of metal impurities such as Na, K, Li, Ca, Mg, and Sr to 100 ppt or less in terms of the total content.

[0003] In general, aqueous solutions of quaternary ammonium compounds are produced by synthesis using tertiary amines and alkyl salts, electrolysis using an electrolytic cell with an ion exchange membrane, etc. For example, aqueous solutions of quaternary ammonium hydroxide are synthesized by subjecting an aqueous solution of quaternary ammonium salt as a raw material to electrolysis, etc. In the aqueous solution of quaternary ammonium hydroxide thus synthesized (or the aqueous solution of quaternary ammonium salt, which is the raw material for obtaining it), the above-mentioned metal impurities are present at a high content level of several hundred ppt or more, which is unsatisfactory from the viewpoint of the defect prevention effect in the semiconductor application.

[0004] Filter treatment is a commonly used method for purifying such crude aqueous solutions of quaternary ammonium compounds. However, although filter treatment is effective in reducing particulate metal impurities, it has the problem that it is almost ineffective in removing dissociated ions due to the limitations of the pore size.

[0005] Adsorption treatment with a cation exchange resin is considered to be effective for removing metal ions from an aqueous solution of a quaternary ammonium compound. However, even with this method, the reduction effect is still not sufficient for the semiconductor applications. For example, in Patent Document 1, this treatment is performed on an aqueous solution of a quaternary ammonium hydroxide compound synthesized by the above-mentioned electrolysis method, but metal ions such as Na ions and Ca ions can only be reduced to the ppb order (see Reference Example 1 in

[0016] , etc.).

[0006] It is also known that the adsorption treatment of a crude aqueous solution of a quaternary ammonium hydroxide compound with a cation exchange resin is also used for the purpose of recovering the quaternary ammonium hydroxide compound component from waste liquid when the aqueous solution of the quaternary ammonium hydroxide compound is used as a photoresist developer for semiconductor manufacturing (for example, Patent Document 2, etc.). Here, in the above Patent Document 2, the strongly acidic cation exchange resin product used in Example 1, which is shown as a representative example of a cation exchange resin, is described in Patent Document 3 (lower right column, page 3) as having a crosslinking degree of 2 to 10%. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 06-025660 [Patent Document 2] JP 2003-190949 A [Patent Document 3] Japanese Patent Application Publication No. 1-98617 Summary of the Invention [Problem to be solved by the invention]

[0008] Even in the case of the above-mentioned photoresist developer waste liquid adsorption treatment using a cation exchange resin, the metal ion reduction effect is often not fully satisfactory. Moreover, according to the study by the present inventors, in this case, even if the selection of the cation exchange resin provides a relatively high metal ion reduction effect at the beginning of the treatment, as the purification continues and the treatment amount increases, the reduction effect rapidly deteriorates. Therefore, the knowledge of metal ion removal when the developer waste liquid is used as the treatment liquid cannot be taken into consideration for the purification of the aqueous quaternary ammonium compound obtained by the above-mentioned synthesis (in other words, with a low organic impurity content), which requires stable production for a long time.

[0009] In light of the above, an object of the present invention is to develop a method for removing metal ions from an aqueous solution of a quaternary ammonium compound having a low content of organic impurities, such as that obtained by synthesis, by which the removal effect can be maintained at a high level even when a large amount of the solution is treated continuously. [Means for solving the problem]

[0010] As a result of extensive research to achieve this objective, the inventors discovered that the above problem could be solved by contacting the treated liquid with a cation exchange resin having a specific degree of crosslinking, thereby completing the present invention.

[0011] That is, the present invention provides a method for producing a purified aqueous solution of a quaternary ammonium compound, which comprises contacting an aqueous solution of a crude quaternary ammonium compound, the aqueous solution of which contains 1000 ppm or less of organic impurities having a molecular weight of 1000 g / mol or more and which also contains metal impurities, with a cation exchange resin having a crosslinking degree of 8 or more and in which the counter ion is a non-metallic ion type. Effect of the Invention

[0012] According to the present invention, metal ions contained in a crude aqueous solution of quaternary ammonium compounds having a low content of organic impurities, such as those obtained by synthesis, can be adsorbed and removed with an excellent reduction effect. This excellent reduction effect can be maintained to a high degree even when a large amount of the aqueous solution of the crude quaternary ammonium compounds is treated. Therefore, the present invention is extremely useful as an industrial production method for a purified aqueous solution of quaternary ammonium compounds. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the present invention, the crude aqueous solution of quaternary ammonium compounds, which is the liquid to be treated and contacted with the cation exchange resin, has a cleanliness level of 1000 ppm or less of organic impurities with a molecular weight of 1000 g / mol or more. In the synthesis of quaternary ammonium compounds, high-purity raw materials are used, so the resulting aqueous solution of quaternary ammonium compounds usually satisfies the above-mentioned requirements for the cleanliness of organic impurities. On the other hand, even if it is the same aqueous solution of quaternary ammonium compounds, when it becomes a waste liquid of photoresist developer discharged during semiconductor manufacturing, it contains various organic impurities with large molecular weights (usually novolac resin derivatives and their decomposition products, etc.) derived from the photoresist, so the requirements for the cleanliness of the organic impurities are not satisfied. In addition, it is possible to reduce some organic impurities with large molecular weights by neutralizing and insolubilizing the photoresist, but various other organic substances are also contained, so the requirements for the cleanliness of the organic impurities are usually not satisfied.

[0014] In addition, even if the organic impurities contained in the crude quaternary ammonium compound aqueous solution have a molecular weight of less than 1000 g / mol, they have almost no effect on the metal ion removal effect of the cation exchange resin. Therefore, the crude quaternary ammonium compound aqueous solution may contain organic impurities with such a low molecular weight, but the content is preferably 3 mass% or less. Such low molecular weight organic impurities are considered to be mixed in from unreacted components or impurities of the raw materials used in the synthesis process of the quaternary ammonium compound aqueous solution, and include organic solvents such as methanol and ethanol, and surfactants.

[0015] The content of the organic impurities having a molecular weight of 1000 g / mol or more in the crude aqueous quaternary ammonium compound solution is more preferably 500 ppm or less, and particularly preferably 100 ppm or less.

[0016] The measurement of organic impurities in the crude quaternary ammonium compound aqueous solution is carried out according to the following procedure. First, a sample of the crude quaternary ammonium compound aqueous solution is injected into a gel permeation chromatography (GPC) column, and the liquid containing 1000 g / mol or more of organic impurities is separated and collected. Then, the TOC concentration of the two liquids, the collected liquid and the eluent used for separation by GPC, is obtained using a total organic carbon (TOC) meter, the TOC concentration of the collected liquid is subtracted from the TOC concentration of the eluent alone, and the value is multiplied by the dilution factor of the crude quaternary ammonium compound aqueous solution in the collected liquid, and this value is taken as the concentration of organic impurities in the crude quaternary ammonium compound aqueous solution. Note that when the amount of liquid collected after passing through the GPC column is small and measurement using a TOC meter is difficult, or when the TOC concentration is too low, it is also possible to measure the concentration of organic impurities by collecting the liquid multiple times or concentrating the liquid.

[0017] In the present invention, the quaternary ammonium compound may be any hydroxide or salt of quaternary ammonium without any restrictions. Examples of quaternary ammonium salts include halide salts such as chloride salts and bromide salts, and carbonate salts (including bicarbonate salts, carbonate salts, and mixtures thereof). Examples of quaternary ammonium ions include those represented by the following general formula: [R4N + ] (In the formula, R represents an alkyl group, a hydroxyalkyl group, or an aryl group, and the four R may be the same group or different groups.) Of the groups represented by R, the alkyl group is preferably one having 4 or less carbon atoms, such as a methyl group, an ethyl group, a propyl group, or a butyl group. The hydroxyalkyl group is preferably one of the above alkyl groups substituted with a hydroxyl group. The aryl group is preferably one having 6 to 7 carbon atoms, such as a phenyl group, a benzyl group, or a tolyl group.

[0018] Specific examples of quaternary ammonium compounds include hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, ethyltrimethylammonium hydroxide, hydroxyethyltrimethylammonium hydroxide, and benzyltrimethylammonium hydroxide; chloride salts such as tetramethylammonium chloride, tetraethylammonium chloride, tetrapropylammonium chloride, tetrabutylammonium chloride, ethyltrimethylammonium chloride, hydroxyethyltrimethylammonium chloride, and benzyltrimethylammonium chloride; bromide salts such as tetramethylammonium bromide, tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, ethyltrimethylammonium bromide, hydroxyethyltrimethylammonium bromide, and benzyltrimethylammonium bromide; tetramethylammonium carbonate, tetraethylammonium carbonate, and Examples of the quaternary ammonium compound include carbonates such as tetrapropylammonium carbonate, tetrabutylammonium carbonate, ethyltrimethylammonium carbonate, hydroxyethyltrimethylammonium carbonate, and benzyltrimethylammonium carbonate, and in particular, quaternary ammonium hydroxide, quaternary ammonium halide, and quaternary ammonium carbonate are preferred, and more preferably, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ethyltrimethylammonium hydroxide, tetramethylammonium chloride, tetraethylammonium chloride, ethyltrimethylammonium chloride, tetramethylammonium bromide, tetraethylammonium bromide, ethyltrimethylammonium bromide, tetramethylammonium carbonate, tetraethylammonium carbonate, and ethyltrimethylammonium carbonate are more preferred, and more preferably, tetramethylammonium hydroxide, tetramethylammonium chloride, tetramethylammonium bromide, and tetramethylammonium carbonate are more preferred. These quaternary ammonium compounds may be one type or a mixture of multiple types.

[0019] The concentration of the quaternary ammonium compound is not particularly limited, but generally, if the adsorption treatment is performed at a high concentration, the amount of liquid passing through the solution can be reduced, and concentration work in the subsequent process is not required, so that the concentration is preferably 10% by mass or more, and more preferably 20% by mass or more. On the other hand, if the concentration of the quaternary ammonium compound becomes too high, crystallization or viscosity increases, so that the concentration is preferably 70% by mass or less, and more preferably 60% by mass or less. In addition, if crystallization occurs at a high concentration, it is sufficient to carry out the treatment within a range that does not reach that concentration. In the present invention, the concentration of the quaternary ammonium compound in the aqueous solution can be measured by ion chromatography or potentiometric titration.

[0020] The water component constituting the crude aqueous solution of a quaternary ammonium compound is preferably as pure as possible, and is more preferably ultrapure water.

[0021] These aqueous solutions of crude quaternary ammonium compounds usually contain metal impurities of 1000 ppt or more, and even at the lowest, exceed 100 ppt. Even with this level of content, when these are used for the semiconductor applications, it is not satisfactory from the viewpoint of suppressing defects, and it becomes necessary to carry out the purification treatment according to the present invention.

[0022] Here, in the present invention, the metal impurities specifically refer to elements consisting of Na, K, Li, Ca, Mg, and Sr, and the content is evaluated as the total content of these elements. Note that, in the present invention, the content of the metal impurities in the aqueous solution of the quaternary ammonium compound refers to a value analyzed by an inductively coupled plasma mass meter (ICP-MS).

[0023] The crude quaternary ammonium compound aqueous solution can be applied from any origin as long as it satisfies the requirements for the content of the organic impurities and metal impurities. Usually, it is preferable to use an aqueous solution of quaternary ammonium hydroxide obtained by synthesis by electrolysis or the like, or an aqueous solution of quaternary ammonium salt that is a raw material for carrying out this. Here, for the production of an aqueous solution of quaternary ammonium hydroxide by electrolysis, an electrolytic cell is generally used in which at least one cation exchange membrane is arranged between an anode and a cathode, and which is provided with a raw material chamber for supplying an aqueous solution of quaternary ammonium salt as a raw material and a base chamber (cathode chamber) in which an aqueous solution of quaternary ammonium hydroxide is produced. In this production method, quaternary ammonium ions pass through the cation exchange membrane arranged on the cathode side, and an aqueous solution of quaternary ammonium hydroxide is produced in the base chamber. In addition, an electrolytic cell in which a plurality of cation exchange membranes, an anion exchange membrane, and a bipolar membrane (a membrane in which a cation exchange membrane and an anion exchange membrane are laminated together) are installed is proposed, and the method can be applied to any of the electrolytic cells.

[0024] In the present invention, the aqueous solution of the crude quaternary ammonium compound is brought into contact with a cation exchange resin, and the impurity metal ions are adsorbed and removed by the cation exchange resin, thereby reducing the content of metal impurities. Since the aqueous solution of the crude quaternary ammonium compound is neutral to basic, the cation exchange resin can be used well whether it is a strong acid cation exchange resin in which the cation exchange group is a sulfonic acid group, or a weak acid cation exchange resin in which the cation exchange group is a carboxyl group, a phenolic hydroxyl group, or the like.

[0025] However, since the crude aqueous solution of quaternary ammonium compounds may be acidic due to the inclusion of a trace amount of acid during the production process, it is preferable to use a strongly acidic cation exchange resin capable of exchange even in the strongly acidic range. Alternatively, the acid may be neutralized with a hydroxide having the same quaternary ammonium ion as the crude aqueous solution of quaternary ammonium compounds before being brought into contact with the weakly acidic cation exchange resin.

[0026] The strongly acidic cation exchange resin generally has a structure in which a sulfonic acid group is introduced into a crosslinkable resin matrix made of a copolymer of a cation exchange group-introducing precursor monovinyl monomer and a crosslinkable monomer. Examples of the cation exchange group-introducing precursor monovinyl monomer include alkyl-substituted styrenes such as styrene, methylstyrene, and ethylstyrene, and halogen-substituted styrenes such as bromostyrene, and these may be used alone or in combination of two or more. As the monovinyl monomer, styrene or a monomer mainly composed of styrene is particularly preferred.

[0027] Examples of the crosslinkable monomer include crosslinkable monomers having multiple vinyl groups such as divinylbenzene, trivinylbenzene, divinyltoluene, divinylnaphthalene, divinylxylene, divinylbiphenyl, bis(vinylphenyl)methane, bis(vinylphenyl)ethane, bis(vinylphenyl)propane, and bis(vinylphenyl)butane, which may be used alone or in combination of two or more. Among these, divinylbenzene is particularly preferred as the crosslinkable monomer.

[0028] On the other hand, examples of the weakly acidic cation exchange resin include copolymers of a monovinyl monomer having the weakly acidic cation exchange group, such as acrylic acid or methacrylic acid, and a crosslinkable monomer. Particularly preferred are acrylic acid-divinylbenzene copolymers and methacrylic acid-divinylbenzene copolymers.

[0029] The greatest feature of the present invention is that the cation exchange resin with which the crude quaternary ammonium compound aqueous solution is contacted has a crosslinking degree of 8 or more and a counter ion of non-metal ion type. As a result, the effect of removing metal ions is maintained at a high level even if a large amount of the crude quaternary ammonium compound aqueous solution is continuously treated. Here, the crosslinking degree of the cation exchange resin is calculated as [weight of crosslinking monomer / weight of total charged monomer)×100] when the resin is produced. In addition, when the cation exchange resin is a strongly acidic cation exchange resin, as explained above, the crosslinking resin base is synthesized first, and the cation exchange group is often introduced in a post-treatment. In the case of a strongly acidic cation exchange resin, the crosslinking degree is calculated without considering the weight of the cation exchange group, which is often introduced in the post-treatment, and without including it in the above formula. In addition, when the crosslinking degree of the cation exchange resin to be used is unknown, the cation exchange resin may be subjected to pyrolysis gas chromatography mass spectrometry (GC / MS) to calculate the ratio of the crosslinking monomer to other monomers.

[0030] Here, the effect of maintaining the metal ion removal effect to a high degree by using a cation exchange resin with a crosslinking degree of 8 or more is an effect that is specifically manifested when a crude quaternary ammonium compound aqueous solution containing a low content of the organic impurities with large molecular weight is used. In other words, in the treatment of photoresist developer wastewater as in Patent Document 2, the organic impurities with large molecular weight are contained in large amounts, so this effect is hardly manifested.

[0031] The reason why the effect of continuously removing the metal ions is specifically exhibited only in the aqueous solution of crude quaternary ammonium compounds with a low content of organic impurities having a large molecular weight is not entirely clear, but the present inventors speculate that it may be due to the following reason: When the cation exchange resin becomes highly rigid, the polymer chains constituting the resin become more entangled, and the resin density increases, making it difficult for ions to diffuse into the inside of the ion exchange resin.

[0032] When the crude aqueous solution of quaternary ammonium compounds is contacted with a cation exchange resin, the ion size of the cations, such as hydrogen ions and metal ions (ionic radius 2 Å or less), does not change significantly in diffusibility into the inside of the particles even if the resin density is high. On the other hand, when the ion size is large, such as quaternary ammonium ions, even if they can easily diffuse into the inside of the particles when the resin density is low, they are gradually hindered in internal diffusibility as the crosslinking strength increases and the resin density increases. As a result, it is presumed that the internal diffusion of quaternary ammonium ions is suppressed in the highly crosslinked cation exchange resin, thereby exhibiting adsorption selectivity for highly diffusible metal ions. Thus, if a cation exchange resin with a crosslinking degree of 8 or more is used, metal ion impurities are adsorbed with high selectivity to quaternary ammonium ions present in large excess in the treated liquid, making it possible to reduce the metal ion concentration.

[0033] However, this selective and excellent removal action is only significantly exerted at the beginning of the purification process when the crude quaternary ammonium compound aqueous solution contains a large amount of organic impurities with a molecular weight of 1000 g / mol or more, exceeding 1000 ppm. This is because, in the crude quaternary ammonium compound aqueous solution, the long molecular chains of the organic impurities are homogeneously dispersed in the liquid until the beginning of the purification process, and have almost no effect on the adsorption properties of the cation exchange resin, but as the purification process continues, they gradually become entangled with the surface of the resin particles, and eventually cover most of the surface. In other words, when most of the particle surface of the cation exchange resin is covered with organic impurities in this way, even metal ions are strongly hindered from diffusing into the inside, and the selective removal action is not smoothly exerted.

[0034] From the viewpoint of achieving a higher level of the metal ion removal effect, the degree of crosslinking of the cation exchange resin is preferably at least 11, and more preferably at least 16. If the degree of crosslinking of the cation exchange resin is too high, the diffusion rate of even metal ions becomes slow, and the capture rate of metals becomes slow, so the degree of crosslinking is preferably at most 30, more preferably at most 25, and particularly preferably at most 22.

[0035] The cation exchange resin may be in any shape, such as a gel type or a macroporous type, but the larger the contact area between the ion exchange resin and the liquid, the easier it is for metal ions to diffuse into the ion exchange resin, so the macroporous type is more preferably used in the present invention.

[0036] In addition, the cation exchange resin used in the present invention preferably has a cation exchange capacity of 1.0 to 5.0 equivalents / L, more preferably 1.5 to 3.0 equivalents / L. The resin body shape of the cation exchange resin is not particularly limited and may be a membrane or the like, but is usually preferably a particulate shape.

[0037] Here, it is necessary to use a non-metal ion type counter ion for the cation exchange resin. That is, the counter ion for the cation exchange resin is usually a hydrogen ion type or a metal ion type, but the metal ion type cannot be used in the present invention because the metal ion present as the counter ion is eluted in the purification process, preventing a reduction in the metal ion concentration in the purified aqueous solution of the quaternary ammonium compound obtained. Therefore, the counter ion for the cation exchange resin should be a cation other than a metal ion, specifically, the hydrogen ion, as well as an ammonium ion (NH4 + ) or primary to quaternary ammonium ions, etc. are used.

[0038] In the present invention, the counter ion of the cation exchange resin is preferably a hydrogen ion type. +) or primary to quaternary ammonium ions, unless the cation is the same quaternary ammonium ion as in the crude aqueous solution of quaternary ammonium compound, the elution of the other cation may cause contamination of the resulting aqueous solution of the purified quaternary ammonium compound with another ammonium compound, making separation difficult.

[0039] On the other hand, in the case of the hydrogen ion type, hydrogen ions are released by exchange with metal ions, but if the crude quaternary ammonium compound is a hydroxide, it is neutralized to water and does not cause contamination, and even if the crude quaternary ammonium compound is not a hydroxide, if the acid derived from the released hydrogen ions is neutralized by adding a hydroxide having the same quaternary ammonium ion as the crude quaternary ammonium compound, the acid becomes the crude quaternary ammonium compound and water, and contamination is easily removed. The hydrogen ion type is also preferable as a part of the counter ion, and in that case, it is preferable that at least 1 mol% is the hydrogen ion type, more preferably at least 3 mol%, particularly preferably at least 10 mol%, and most preferably at least 20 mol%.

[0040] The cation exchange resin with a crosslinking degree of 8 or more and a non-metal ion type counter ion can be obtained as a non-metal ion type by contacting it with an aqueous solution containing cations other than metal ions to remove the metal ions when only metal ion type counter ions are available or when a certain amount of metal ions is contained and the metal ion concentration is to be reduced. However, as mentioned above, in a cation exchange resin with a high crosslinking degree, since large cations such as quaternary ammonium ions are difficult to diffuse into the resin, it is preferable to contact it with an aqueous solution containing small cations that can easily penetrate into the resin and be quickly exchanged with metal ions. The preferred form is an aqueous solution in which the cations are hydrogen ions, that is, it is preferable to contact it with an acid.

[0041] In the present invention, the cation exchange resin has a crosslinking degree of 8 or more and has a hydrogen ion type counter ion, and is used in contact with an aqueous solution of a quaternary ammonium compound having the same quaternary ammonium ion as the aqueous solution of the crude quaternary ammonium compound. That is, according to this treatment, some of the counter ions of the cation exchange resin remain hydrogen ions due to the influence of the diffusibility inhibition of the quaternary ammonium ion, but a significant amount of the hydrogen ions are exchanged for the same quaternary ammonium ion as the aqueous solution of the crude quaternary ammonium compound. Thus, the cation exchange resin obtained has a significant proportion of counter ions exchanged for the same quaternary ammonium ion as the aqueous solution of the crude quaternary ammonium compound. If the cation exchange resin is in such a state, the quaternary ammonium ions of the treated solution are adsorbed to the cation exchange resin at the start of the purification of the aqueous solution of the crude quaternary ammonium compound according to the present invention, and therefore the phenomenon in which the purified aqueous solution of the quaternary ammonium compound is produced with a temporary decrease in concentration can be prevented, which is preferable.

[0042] Even after contacting the aqueous solution of a quaternary ammonium compound having the same quaternary ammonium ion as the aqueous solution of the crude quaternary ammonium compound as described above, some hydrogen ions remain as counter ions of the highly crosslinked cation exchange resin. The preferred amount of the hydrogen ions remaining is within the range described above for the amount of the hydrogen ion type counter ions.

[0043] As mentioned above, the counter ions of the cation exchange resin are non-metal ions, but this does not mean that all the counter ions are completely other than metal ions, and as long as the effect is not significantly affected, it is acceptable for metal ions to be inevitably mixed in. Specifically, metal ions are acceptable within the scope of the present invention if they are contained in an amount of 3 mol % or less, preferably 0.1 mol % or less, and particularly preferably 0.001 mol % or less of the counter ions.

[0044] In the present invention, the counter ions of the cation exchange resin are brought into contact with an acid to elute metal ions and nonmetallic ions other than hydrogen ions, and each component can be quantified by ion chromatography. Hydrogen ions can be quantified by contacting the resin with a salt to elute hydrogen ions, and then performing neutralization titration.

[0045] Here, the aqueous acid solution used for contact with the cation exchange resin having a metal ion type counter ion is an aqueous inorganic acid solution such as sulfuric acid, hydrochloric acid, or nitric acid, and from the viewpoint of preventing deterioration of the resin material, it is preferable to use an aqueous hydrochloric acid solution or an aqueous sulfuric acid solution. The concentration of the acid can be used without any restrictions, but since contact with a high concentration acid may cause cracks or destruction due to the counter ion being replaced in a short time and causing a sudden change in volume, it is preferably 1 mol / L or less, more preferably 0.5 mol / L or less, and even more preferably 0.3 mol / L or less. It is preferable to treat with an acid equivalent to 1.2 to 5 times the total amount of exchange groups of the cation exchange resin used, and more preferably 1.5 to 3 times the total amount of acid.

[0046] The contact treatment may be a batch type or a liquid-passing type, but is not particularly limited. In the case of a liquid-passing type in which a resin tower is formed, either an ascending flow or a descending flow may be used, and it is preferable to pass an acid containing an amount equivalent to at least three times the amount of exchange groups of the ion exchange resin to be treated, and although there is no particular specification for the liquid passing speed, it is preferable to perform the treatment in the range of SV=1 to 20 (1 / hr) from the viewpoint of treatment time and efficiency. In addition, in the case of a batch type, it is preferable to exchange the liquid three or more times with an acid equivalent to 3 to 15 times the total amount of exchange groups of the cation exchange resin to be treated.

[0047] In addition, if the content of metal ions contained in the acid aqueous solution is high, metal ions will remain in the cation exchange resin depending on the concentration, and the amount of metal ions exchanged during purification may decrease, or in some cases, they may be released and cause contamination. For this reason, it is preferable that the total content of metal impurities consisting of Na, K, Li, Ca, Mg, and Sr contained in the acid aqueous solution is 100 ppt or less, more preferably 10 ppt or less, and even more preferably 1 ppt or less. Furthermore, it is preferable that the total content of metal impurities consisting of Fe, Ni, Cu, and Pb in the acid aqueous solution is also 100 ppt or less, more preferably 10 ppt or less, and even more preferably 1 ppt or less.

[0048] After contacting with the aqueous acid solution, the cation exchange resin is preferably washed with ultrapure water. This removes excess acid that has not been incorporated as a counter ion by adhering to the surface of the resin, and prevents the acid from being mixed into the subsequent steps. In particular, when the quaternary ammonium compound contained in the crude aqueous quaternary ammonium compound solution is a quaternary ammonium hydroxide, residual acid in the cation exchange resin may cause a sudden heat generation due to a neutralization reaction, which may cause the resin to be destroyed due to the sudden swelling of the resin. Therefore, washing with ultrapure water is preferably performed.

[0049] In addition, when the counter ion is hydrogen ion type and the cation exchange resin is contacted with an aqueous solution of a quaternary ammonium compound having the same quaternary ammonium ion as the aqueous solution of the crude quaternary ammonium compound, the aqueous solution of the quaternary ammonium compound is preferably used with the same concentration, contact method, and metal ion content as those described for the aqueous acid solution. Similarly, it is preferable to wash the cation exchange resin with ultrapure water after contacting with the aqueous solution of the quaternary ammonium compound.

[0050] Next, in the present invention, the method of contacting the cation exchange resin with the crude aqueous solution of quaternary ammonium compound may be any type, such as a batch type or a liquid-passing type, but industrially, the liquid-passing type is preferable. In the liquid-passing type, purification is performed by passing the liquid through a resin tower. The liquid passing direction may be either an upward flow or a downward flow, and from the viewpoint of increasing purification efficiency, a downward flow is preferable. The liquid passing conditions are preferably a space velocity SV of 1 to 20 (1 / hr), more preferably 5 to 20 (1 / hr).

[0051] The treatment amount of the crude quaternary ammonium compound aqueous solution to be contacted is generally 100 (L / L-resin) or more for efficiency. As described above, the excellent effect of removing metal ions in the method of the present invention is particularly exhibited when a large amount of the crude quaternary ammonium compound aqueous solution is treated, so it is more effective to set the treatment amount under conditions of 2000 (L / L-resin) or more, more preferably 10,000 (L / L-resin) or more of cation exchange resin relative to the crude quaternary ammonium compound aqueous solution. However, if the treatment amount is still too large, the effect of removing metal ions decreases, so the treatment amount is generally set to 10 8 (L / L-resin) or less, particularly preferably 50,000 (L / L-resin) or less.

[0052] It is efficient to subject the cation exchange resin in which the metal ion removal effect has been reduced in this way to the above-mentioned acid treatment as a resin regeneration treatment, and then resume the flow of liquid and repeat purification. In addition, the liquid may be passed through two or more resin towers in succession.

[0053] On the other hand, in the case of purification by a batch system, it is preferable to immerse the resin in an aqueous solution of a crude quaternary ammonium compound at 200 L / L or more in order to significantly exhibit the excellent effect of removing the metal ions. It is also preferable to repeat the batch treatment, since the metal ions can be further reduced. The number of repetitions is preferably 2 to 5 times.

[0054] In the method of the present invention, when particulate metal impurities are contained in the aqueous solution of the crude quaternary ammonium compound, it is preferable to remove them by performing a filter treatment before or after the contact with the cation exchange resin. If particulate metal impurities or resin particles are contained in the aqueous solution of the crude quaternary ammonium compound, the action of removing metal ions by the cation exchange resin in the present invention may be hindered, or in the case of a flow-through type, clogging may occur, so it is preferable to perform a filter treatment as a pretreatment. In addition, since there is a risk that particulate metal impurities remaining after contact with the cation exchange resin and, in some cases, broken pieces of the cation exchange resin may be mixed in, it is also preferable to perform the filter treatment as a posttreatment.

[0055] The average pore size of the filter used is preferably 1 μm or less, and more preferably 0.02 to 1 μm. When the average pore size of the filter is unknown, the value measured by the bubble point method is used as the average pore size.

[0056] The inner walls of the equipment such as containers, tanks, resin towers, and piping used to carry out the production method of the present invention are desirably made of a material that is resistant to chemicals and minimizes metal contamination. Therefore, it is preferable that they are made of or lined with polyethylene, polypropylene, or fluororesin materials. In particular, fluororesin is optimal from the viewpoint of preventing metal contamination. It is preferable to clean the surfaces of these members before use, for example, by cleaning them with an aqueous solution of a quaternary ammonium hydroxide compound or an acid.

[0057] By the above method, a purified aqueous solution of quaternary ammonium compound with reduced metal ions can be effectively produced. Specifically, it is possible to obtain an aqueous solution of quaternary ammonium compound in which the total content of metal impurities consisting of Na, K, Li, Ca, Mg, and Sr is 100 ppt or less, more preferably 50 ppt or less, and even more preferably 20 ppt or less. The aqueous solution of quaternary ammonium compound can also have the content of each of these metal elements be 30 ppt or less, more preferably 10 ppt or less, and even more preferably 5 ppt or less.

[0058] In addition, when the quaternary ammonium compound is a hydroxide salt, the aqueous solution of the quaternary ammonium compound may take the form of anion or non-ion in some metal elements other than the above-mentioned metal elements due to its strong alkalinity, and the removal effect may be insufficient. However, when the quaternary ammonium compound is a halogenated quaternary ammonium compound or a carbonated quaternary ammonium compound other than the hydroxide, the effect of reducing the other metal elements is also high. Therefore, when the counter ion is other than the hydroxide, it is also possible to obtain an aqueous solution of the quaternary ammonium compound in which the total content of metal impurities consisting of Fe, Ni, Cu, and Pb is 100 ppt or less, more preferably 50 ppt or less, and even more preferably 20 ppt or less. EXAMPLES

[0059] Examples are given below to specifically explain the present invention, but the present invention is not limited to these. The physical properties measured in the examples and comparative examples were determined by the following methods.

[0060] 1) Content of metal impurities in aqueous solutions of quaternary ammonium compounds The concentrations of Na, K, Li, Ca, Mg, Sr, Fe, Ni, Cu, and Pb were measured using an inductively coupled plasma mass meter (ICP-MS). The lower limit of measurement was 1 ppt, and values ​​below 1 ppt were considered to be <1 ppt.

[0061] 2) The content of organic impurities with a molecular weight of 1000 g / mol or more contained in the aqueous solution of quaternary ammonium compounds A sample of the crude quaternary ammonium compound aqueous solution was injected into a GPC column, and the solution containing 1000 g / mol or more of organic impurities was separated and collected. The TOC concentration of the collected solution and the eluent used for separation by GPC were each measured using a TOC meter. The TOC concentration of the eluent was subtracted from the TOC concentration of the collected solution, and this was multiplied by the dilution factor of the crude quaternary ammonium compound aqueous solution in the collected solution to obtain the concentration of organic impurities in the crude quaternary ammonium compound aqueous solution.

[0062] 3) Proportion of hydrogen ions contained in the counter ions of the cation exchange resin The cation exchange resin was contacted with sodium chloride to elute hydrogen ions, and the resulting liquid was subjected to neutralization titration with sodium hydroxide to quantify the hydrogen ions contained in the counter ions. The same cation exchange resin was also contacted with hydrochloric acid (where all counter ions were hydrogen ions), washed with ultrapure water, and contacted again with sodium chloride to quantify the hydrogen ions in the resulting liquid by neutralization titration with sodium hydroxide to determine the amount of exchange groups on the cation exchange resin. The proportion of hydrogen ions was determined by dividing the amount of exchange groups by the amount of hydrogen ions contained in the counter ions on the cation exchange resin, which was determined initially.

[0063] Example 1 A powder of synthetic tetramethylammonium chloride (commercially available from Company A, general grade) was dissolved in water to adjust the mass to 60%, to prepare a crude tetramethylammonium chloride aqueous solution. The content of metal impurities in this crude tetramethylammonium chloride aqueous solution was measured, and the total content of metal impurities consisting of Na, K, Li, Ca, Mg, and Sr is shown in Table 1, and the total content of metal impurities consisting of Fe, Ni, Cu, and Pb is shown in Table 2. The content of organic impurities with a molecular weight of 1000 g / mol or more (large molecular weight organic impurities) was also measured, and was found to be 372 ppm.

[0064] Next, 50 mL of Amberlite 200CT Na (crosslinking degree 20, cation exchange capacity 1.7 equivalents / L, manufactured by Organo Corporation), a strong acid ion exchange resin, was packed into a column having a diameter of 22 mm and a length of 750 mm. 1) Ultrapure water cleaning, 2) Treatment with 0.3 mol / L hydrochloric acid, 3) Ultrapure water treatment, 4) Treatment with 0.3 mol / L tetramethylammonium hydroxide aqueous solution 5) Ultrapure water treatment The amount of each liquid passed was 600 mL, and the space velocity was SV=5 (1 / hr).

[0065] The 0.3 mol / L hydrochloric acid and 0.3 mol / L tetramethylammonium hydroxide aqueous solution each had a total content of metal impurities consisting of Na, K, Li, Ca, Mg, and Sr of 100 ppt or less, and a total content of metal impurities consisting of Fe, Ni, Cu, and Pb of 100 ppt or less. The ultrapure water used had a total content of metal impurities consisting of Na, K, Li, Ca, Mg, Sr, Fe, Ni, Cu, and Pb of 1 ppt or less. The proportion of hydrogen ions contained in the counter ions of the strongly acidic ion exchange resin after the pretreatment was measured and found to be 20 mol%.

[0066] A crude tetramethylammonium chloride aqueous solution was passed through the column under the conditions of 1050L and SV=20 (1 / hr). After the amount of the solution passed reached 10L (200L / L-resin), 100L (2000L / L-resin), 500L (10000L / L-resin), and 1000L (20000L / L-resin), 10L of each solution was sampled and the content of metal impurities was measured. The results are shown in Tables 1 and 2, respectively.

[0067] Example 2 The same operation as in Example 1 was carried out except that the strongly acidic ion exchange resin used in Example 1 was changed to Diaion UBK16 (crosslinking degree 16, cation exchange capacity 2.3 equivalents / L, Mitsubishi Chemical Corporation). The ratio of hydrogen ions contained in the counter ions of the strongly acidic ion exchange resin after the pretreatment was measured and found to be 11 mol%. The measurement results of the metal impurity content are shown in Tables 1 and 2 above, respectively.

[0068] Example 3 The same operation as in Example 1 was carried out except that the strongly acidic ion exchange resin used in Example 1 was changed to Diaion SK112 (crosslinking degree 12, cation exchange capacity 2.1 equivalents / L, manufactured by Mitsubishi Chemical Corporation). The ratio of hydrogen ions contained in the counter ions of the strongly acidic ion exchange resin after the pretreatment was measured at this time and found to be 3 mol%. The measurement results of the metal impurity content are shown in Tables 1 and 2 above, respectively.

[0069] Example 4 In Example 1, the strongly acidic ion exchange resin used was changed to Diaion SK1B (crosslinking degree 8, cation exchange capacity 2.0 equivalents / L, manufactured by Mitsubishi Chemical Corporation), but the same operation as in Example 1 was performed. The ratio of hydrogen ions contained in the counter ions of the strongly acidic ion exchange resin after the pretreatment was measured at this time, and it was 1 mol%. The measurement results of the metal impurity content are shown in Tables 1 and 2 above, respectively.

[0070] Comparative Example 1 The same operation as in Example 1 was carried out except that the strongly acidic ion exchange resin used in Example 1 was changed to Diaion PK212 (crosslinking degree 6, cation exchange capacity 1.5 equivalents / L, manufactured by Mitsubishi Chemical Corporation). The ratio of hydrogen ions contained in the counter ions of the strongly acidic ion exchange resin after the pretreatment was measured and found to be 0.1 mol% or less. The measurement results of the metal impurity content are shown in Tables 1 and 2 above, respectively.

[0071] [Table 1]

[0072] [Table 2]

[0073] Comparative Example 2 Aqueous tetramethylammonium hydroxide wastewater discharged from a liquid crystal display factory was neutralized with hydrochloric acid, the insolubilized resist was filtered, and then concentrated by evaporation. This neutralization process turned tetramethylammonium hydroxide into tetramethylammonium chloride, and the concentration by evaporation was adjusted so that tetramethylammonium chloride was 60% by mass, and used as a crude aqueous tetramethylammonium chloride solution. The metal impurity content of this solution was measured, and the results are shown in Tables 3 and 4. The content of organic impurities with a molecular weight of 1000 g / mol or more was also measured, and was found to be 1267 ppm.

[0074] The thus-prepared crude tetramethylammonium chloride aqueous solution was subjected to measurement of the metal impurity content by the same operation as in Example 1. The liquid for measuring the metal impurity content was collected in an amount of 10 L (200 L / L-resin) and 100 L (2000 L / L-resin). The measurement results of the metal impurity content are shown in Tables 3 and 4, respectively.

[0075] [Table 3]

[0076] [Table 4]

[0077] Examples 5 to 8 and Comparative Example 3 A synthetic aqueous solution of tetramethylammonium hydroxide (high purity grade, commercially available from Company B) adjusted to 25% by mass was used as the crude aqueous solution of tetramethylammonium hydroxide. The metal impurity content of this solution was measured, and the results are shown in Tables 5 and 6. The content of organic impurities with a molecular weight of 1000 g / mol or more was also measured, and was found to be 43 ppm.

[0078] Except for using the thus prepared crude aqueous tetramethylammonium hydroxide solution, the same operations as in Examples 1 to 4 and Comparative Example 1 were carried out. The measurement results of the metal impurity contents are shown in Tables 5 and 6 above, respectively.

[0079] [Table 5]

[0080] [Table 6]

[0081] In each of the Examples in which a crude aqueous solution of quaternary ammonium containing 1000 ppm or less of organic impurities with a molecular weight of 1000 g / mol or more was treated, contact with a cation exchange resin having a crosslinking degree of 8 or more and a non-metallic ion type counter ion produced an excellent effect of reducing the concentration of metal impurities in all cases at the beginning of treatment when the flow rate was 10 L (200 L / L-resin), and this effect was maintained up to at least 100 L (2000 L / L-resin).

[0082] In contrast, in Comparative Examples 1 and 3, in which the degree of crosslinking of the cation exchange resin contacted with the crude aqueous quaternary ammonium solution was less than 8, the effect of reducing the metal impurity concentration was not achieved even when the amount of liquid passed was 100 L (2000 L / L-resin).

[0083] Furthermore, in Comparative Example 2, in which the crude aqueous quaternary ammonium solution to be treated contained a large amount of organic impurities with a molecular weight of 1000 g / mol or more exceeding 1000 ppm, the excellent effect of reducing the metal impurity concentration in each of the above-mentioned Examples was high to a certain extent at the beginning of the treatment when the amount of liquid passed was 10 L (200 L / L-resin), but the effect rapidly decreased when the amount of liquid passed was continued to 100 L (2000 L / L-resin).

Claims

1. A method for producing a purified aqueous solution of a quaternary ammonium compound, comprising contacting an aqueous solution of a crude quaternary ammonium compound, the aqueous solution of which contains 1000 ppm or less of organic impurities having a molecular weight of 1000 g / mol or more and which contains metal impurities, with a cation exchange resin having a crosslinking degree of 8 or more and in which the counter ion is a non-metal ion type.

2. 2. The method for producing a purified aqueous solution of a quaternary ammonium compound according to claim 1, wherein the degree of crosslinking of the cation exchange resin is 11 to 30.

3. 3. The method for producing a purified aqueous solution of a quaternary ammonium compound according to claim 1, wherein the cation exchange resin is a strongly acidic cation exchange resin.

4. The method for producing a purified aqueous solution of a quaternary ammonium compound according to any one of claims 1 to 3, wherein the contact of the crude aqueous solution of a quaternary ammonium compound with the cation exchange resin is carried out in a flow-through manner, and the contact is carried out under conditions of a space velocity SV of 1 to 20 (1 / hr) and a treatment amount of the crude aqueous solution of a quaternary ammonium compound with the cation exchange resin of 2000 (L / L-resin) or more.

5. The method for producing a purified aqueous solution of a quaternary ammonium compound according to any one of claims 1 to 4, wherein the cation exchange resin has a crosslinking degree of 8 or more and has non-metal ion-type counter ions, and at least 1 mol % of the counter ions are hydrogen ion-type.

6. As a cation exchange resin having a crosslinking degree of 8 or more and a non-metal ion type counter ion, The method for producing the purified aqueous solution of a quaternary ammonium compound according to any one of claims 1 to 5, wherein a cation exchange resin having the same crosslinking degree and a counter ion of a metal ion type is contacted with an aqueous acid solution to obtain the cation exchange resin.

7. As a cation exchange resin having a crosslinking degree of 8 or more and a non-metal ion type counter ion, The method for producing a purified aqueous solution of a quaternary ammonium compound according to any one of claims 1 to 6, wherein a cation exchange resin having the same crosslinking degree and a counter ion of hydrogen ion type is contacted with an aqueous solution of a quaternary ammonium compound having the same quaternary ammonium ion as that of the crude aqueous solution of a quaternary ammonium compound.

8. 8. The method for producing a purified aqueous quaternary ammonium compound solution according to any one of 1 to 7, wherein the crude aqueous quaternary ammonium compound solution is a crude aqueous quaternary ammonium hydroxide solution, a crude aqueous quaternary ammonium halide solution, or a crude aqueous quaternary ammonium carbonate solution.

9. An aqueous solution of a quaternary ammonium compound having a total content of metal impurities of Na, K, Li, Ca, Mg, and Sr of 100 ppt or less.

10. 10. The aqueous solution of a quaternary ammonium compound according to claim 9, wherein the quaternary ammonium compound is a quaternary ammonium hydroxide compound, a quaternary ammonium halide compound, or a quaternary ammonium carbonate compound.

11. 10. The aqueous solution of a quaternary ammonium compound according to claim 9, wherein the quaternary ammonium compound is a quaternary ammonium halide compound or a quaternary ammonium carbonate compound, and further contains no more than 100 ppt of metal impurities consisting of Fe, Ni, Cu, and Pb.

Citation Information

Patent Citations

  • Copolymer due to polymerization of glycolic acid and lactic acid

    JP1989098617A

  • Infrared-visible wavelength upward shifting material

    JP1994025660A

  • Method for regeneration of photoresist developing waste solution

    JP2003190949A